Systematic study of magnetar outbursts. Issue 1 (13th October 2017) - Coti Zelati, Francesco; Rea, Nanda; Pons, José A.; Campana, Sergio; Esposito, Paolo
Abstract: We present the results of the systematic study of all magnetar outbursts observed to date, through a reanalysis of data acquired in about 1100 X-ray observations. We track the temporal evolution of the outbursts' soft X-ray spectral properties and the luminosities of the single spectral components as well as of the total emission. We model empirically all outburst light curves, and estimate the characteristic decay time-scales as well as the energetics involved. We investigate the link between different parameters (e.g. the luminosity at the peak of the outburst and in quiescence, the maximum luminosity increase, the decay time-scale and energy of the outburst, the neutron star surface dipolar magnetic field and characteristic age, etc.), and unveil several correlations among these quantities. We discuss our results in the context of the internal crustal heating and twisted bundle models for magnetar outbursts. This study is complemented by the Magnetar Outburst Online Catalogue (http://magnetars.ice.csic.es ), an interactive data base where the user can plot any combination of the parameters derived in this work, and download all data.